A g-C3N4-based heterogeneous photocatalyst for visible light mediated aerobic benzylic C–H oxygenations. Issue 22 (18th October 2019) - Geng, Pengxin; Tang, Yurong; Pan, Guanglong; Wang, Wentao; Hu, Jinchuan; Cai, Yunfei
Abstract : A visible light mediated metal-free heterogeneous photocatalytic system has been developed for highly efficient benzylic C–H oxygenations utilizing graphitic carbon nitride (g-C3 N4 ) as a recyclable, nontoxic and low cost photocatalyst. Abstract : A metal-free heterogeneous photocatalytic system has been developed for highly efficient benzylic C–H oxygenations using oxygen as an oxidant. This visible light mediated oxidation reaction utilizes graphitic carbon nitride (g-C3 N4 ) as a recyclable, nontoxic and low cost photocatalyst. Mild reaction conditions allow for the generation of synthetically and biologically valued isochromannones, phthalides, isoquinolinones, isoindolinones and xanthones from readily accessible alkyl aromatic precursors in good yields. The heterogeneous nature of the g-C3 N4 catalytic system enables easy recovery and recycling as well as the use in multiple runs without loss of activity. The synthetic utility of this "green" methodology was further demonstrated by applying in bioactive and drug valued target syntheses.